Prediksi Produksi Gas Metana dan Dampak Lingkungan dari Kegiatan Landfilling di TPA Griyo Mulyo, Kabupaten Sidoarjo dengan menggunakan Kombinasi Permodelan LandGEM dan OpenLCA - Praditya S. Ardisty Sitogasa; Ahmad Aufinal Muna (Prosiding ESEC, 2023)
This journal discusses predictions of methane gas production and the environmental impact of waste management at the Griyo Mulyo Final Disposal Site (TPA). This research uses a combination of LandGEM and OpenLCA modeling approaches to estimate methane gas production from waste decomposition and the associated environmental impacts. The predicted results of methane gas production from the Griyo Mulyo landfill show variability in methane gas emissions which can occur due to factors such as the volume of incoming waste, and varying degradation conditions over time. Projection of methane gas production using the LandGEM model for the 2020-2030 period with an average temperature parameter of 30°C, the results show peak methane gas production in 2026, with a value of 6.03 Gg/year for Default CAA-Conventional and 2.92 Gg/ year for Inventory Default. Environmental impact analysis using OpenLCA on the Griyo Mulyo TPA landfill in 2023 shows a significant impact on climate change, human toxicity and marine ecosystems. Greenhouse gas emissions reached 1.59 million kg CO2eq, while human and marine ecosystem toxicity reached 18,200 kg and 418 kg 1.4-DB eq, respectively. There are also impacts on air quality and the ozone layer, although to a lesser extent. There are no significant impacts related to abiotic resource exploitation, acidification, or eutrophication. This analysis highlights the importance of more sustainable waste management in the future